Joint effects of paraoxonase 1 rs662 polymorphism and vitamins C/E intake on coronary artery disease severity (Gensini and SYNTAX scores) and lipid profile in patients undergoing coronary angiography - Darand, Mina; Salehi-Abargouei, Amin; Vahidi Mehrjardi, Mohammad Yahya; Feizi, Awat; Seyedhossaini, Seyed Mustafa; Askari, Gholamreza (Frontiers in Nutrition, 2023)
Introduction: Considering the emergence of the concept of personalized nutrition in recent years and its importance in the treatment of diseases, the purpose of this study was to investigate the interaction of paraoxonase (PON)1 rs662 polymorphism and vitamin C/E intake on coronary artery disease (CAD) severity and lipid profile in patients undergoing diagnostic angiography. Methods: This cross-sectional study was carried out on 428 patients undergoing angiography. The PON-1 genotypes were detected by the polymerase chain reaction-restriction fragment length polymorphism technique. Dietary intake was obtained using a valid questionnaire. Results: After adjustment for potential confounders, R allele carriers (RR+RQ) have lower HDL-C levels than non-carriers (QQ) (P-value≤0.05). On the other hand, higher consumption of vitamin C was associated with a reduced risk of high total cholesterol (OR: 0.42, 95% CI 0.23-0.75, P = 0.003) and low-density lipoprotein cholesterol (OR: 0.49, 95% CI 0.25-0.96, P = 0.038) and an increased risk of low high-density lipoprotein cholesterol (OR: 1.88, 95% CI 1.03-3.42, P = 0.037). Furthermore, a significant interaction was observed between vitamin C intake and genotypes of rs66 polymorphism on LDL-C (P-value= 0.050). In detail, the R-allele carriers with lower vitamin C intake had higher LDL-C levels than QQ genotype carriers. No significant interaction was found between vitamin E intake and rs662 polymorphism genotypes on the Gensini and SYNTAX scores and lipid profile (P-value>0.05). Conclusion: The novel finding of the present study was the existence of a significant interaction between rs662 polymorphism and vitamin C intake on LDL-C. More specifically, R allele carriers with lower vitamin C intake were susceptible to higher LDL-C.